Analysis of hair zinc concentration changes in women during perimenopausal transition - Wlaźlak, Edyta; Dunicz-Sokolowska, Aldona; Surkont, Grzegorz; Stetkiewicz, Tomasz; Graczyk, Alfreda (Menopause Review/Przegląd Menopauzalny, 2007)
Analysis of concentrations of hair bioelements seems to be a promising method of initial diagnostics. Zinc plays a vital role in life processes. Aim of the study: The aim of the study was to define zinc concentration in hair of perimenopausal women. Material and methods: In this paper we analyze the results of hair zinc concentration in 258 Polish women aged 42-58. Results: Decreasing age-related tendencies were observed. Conclusions: Hair zinc concentrations decrease with age in the examined group of perimenopausal women.